Data Security In Cloud Using Novel Encryption And Decryption Algorithm (Neda) - M. Arunadevi, Dr. V. Sathya (International Journal of Advanced Science and Technology, 2020)
- Cloud computing is a model for empowering convenient, on-request network access to a shared pool of configurable computing resources that can be rapidly provisioned and delivered with minimal management effort or service provider interaction .Cloud computing has developed into a mainstream part of the IT industry. Cloud computing gives a scope of hardware and software resources to its customers, which they can access through the internet. With the rapid development of cloud computing, different security issues identified with confidentiality and integrity are showing up. For enterprises the main issue is likewise security however with various visions. For them elite might be not as critical as academia. We proposed the novel encryption and decryption method. Traditional encryption techniques give security to data while it is put away and transmitted, however not while it is processed. Consequently traditional encryption techniques are sufficiently not to secure data totally. Decryption presents a resolution to this obstacle by permitting computation on encrypted data.